Dust oscillons with finite OAM and dust self-gravity effects. (21st March 2019) - Ali, S; Bukhari, S; Ikram, M; Mendonca, J T
Abstract: Dust oscillons, or dust waves carrying distinct states of orbital angular momentum (OAM), are studied in a self-gravitating unmagnetized dusty plasma, whose constituents are the inertialess electrons and ions with negatively charged mobile massive dust grains. Starting from the linearized fluid equations, an evolution equation in terms of dust density perturbation is derived. By using the beam type solution, the wave is assumed to propagate around the beam axis with slowly varying amplitude proportional to exp(ikz). It leads to a paraxial equation of the wave that admits more generalized Laguerre–Gaussian beam solutions within paraxial limits. It is also shown that dust oscillons carry finite amount of energy flux and OAM density and are modified significantly by the azimuthal mode index and group velocity including the dust Jeans effects. Numerically, the dust Jeans frequency, azimuthal phase angle, as well as radial and azimuthal mode indices have strong dependence on the profiles of dust density perturbations. The present findings may prove useful to understand the dynamics of dust oscillons caused by the Brillouin backscattering of laser beams in a self-gravitating dusty plasma.